Monetary policy with forward-looking rules: The Swiss case - Nicolas A. Cuche (Swiss National Bank, Study Center Gerzensee, 2000)
We estimate monetary policy rules in Switzerland for 1981-1997. In addition to an inflation gap, we find that forward-looking rules with output and exchange rate gaps nicely fit monetary aggregates as well as the call rate. We split the sample in 1990 when the Swiss National Bank replaced annual targets by medium-term targets for its official policy instrument, the monetary base. We find then that our rule best describes M0 and M1 before 1990 and only the call rate after 1990. Moreover, such small open economy rules are robust with respect to different central bank information sets.
Keywords: E52; E58; 330; Exchange rate; Monetary policy instrument; Output gap; Robustness; Rule; Switzerland; Geldpolitik; Wirkungsanalyse; Schweiz